Surgical Treatment of Thoracic Myelopathy Secondary to Ossification of Ligamentum Flavum - Arora, Rajnish K.; Jaiswal, Manish; Mittal, Radhey S.; Arora, Poonam (Indian Journal of Neurosurgery, 2016)
Objectives We retrospectively studied the risk factors, clinical manifestations, radiological aspects, surgical treatment, and prognostic factors in 143 patients of thoracic ossification of ligamentum flavum (OLF).Methods A total of 143 patients who underwent surgical treatment for thoracic myelopathy secondary to OLF between 1989 and 2010 were studied retrospectively. Preoperative and postoperative neurological data were reviewed and the correlation between the variables of patient characteristics, preoperative duration of symptoms, preoperative neurological status, and the functional outcome were analyzed. The male to female ratio was 1.5:1. In total, 114 patients (79.72%) were in the 4th to 6th decade of life. Only two cases (1.4%) were of less than 20-year age group. The lower thoracic region (D9–D12) was most commonly affected (61.5%). Four patients had long segment involvement (≥7 levels) and eight patients had two separate levels of involvement. Associated fluorosis was observed in 32 patients (22.37%). All patients underwent wide decompressive laminectomy with medial one-third facetectomy and OLF was resected. The part of dura adherent to OLF or calcified is also removed with it and duroplasty done if required. The average follow-up was 5 years.Outcome In all, 86 patients (60.13%) were able to do their job with mild neurological deficit such as spasticity and impairment of joint position sense. Twenty-eight patients (19.58%) were back to some job with limitation but were independent for their routine work. Sixteen patients (11.18%) improved but still required help for their routine work while thirteen patients (9.09%) were bed-ridden at last follow-up. Most common complications observed were cerebrospinal fluid leak (7.69%), neurological deterioration (8.39%), and infection (4.89%). Five (3.4%) patients required second surgery for ossification at other level during follow-up.
Keywords: ossification of ligamentum flavum; surgical treatment; prognostic factors